Recent natural resource management achievements - Chaudhari, S K (Indian Farming, 2019)
Natural Resource Management Division of ICAR is conducting basic and strategic researches to develop technologies for conservation, management and sustainable utilization of the natural resources ensuring food, nutritional and environmental security in the country. Its vision is sustainable management of natural resources for achieving food, nutritional, environmental and livelihood security in the country.